Mutual Insurance in the Village and Beyond - Clive Bell; Hans Gersbach; Hans Haller (Institute of Labor Economics (IZA), 2024)
When formal insurance is unavailable, mutual insurance among households can serve as an alternative. This paper analyzes a game between economic agents facing uncertainty and maximizing discounted utility without enforceable contracts or access to capital markets. While autarky is always a possible outcome, under high discount factors, a mutually beneficial trigger-strategy equilibrium can be achieved. Full insurance is possible with strongly negatively correlated endowments, while partial insurance is generally feasible. The analysis highlights environments wherein varying levels of insurance can emerge, with applications to real-world institutional contexts.
Keywords: C72; C73; D80; G20; O11; 330; mutual insurance; risk sharing; group formation